Maya sculpture of Copán the iconography - Baudez, Claude F. 1932-2013 (Univ. of Oklahoma Press, 1994)
Part I is a description of the specific motifs on each monument. Baudez identifies and deciphers the individual elements and shows how they were combined to produce meaningful iconographic messages. The architectural sculpture is shown to express the meaning and function of the buildings and complexes, many of which were designed to represent the sky, earth, and underworld and served as stages for rituals. Photographs and drawings augment the textual descriptions, clarifying the intricate forms
Keywords: Iconografie; Maya's; Mayas - Politique et gouvernement; Plastische kunst; Religion maya; Sculpture maya - Honduras - Copán (site archéologique); Politik; Maya mythology; Maya sculpture -- Honduras -- Copán Site; Mayas -- Politics and government; Relief; Ikonographie; Copán (Honduras; site archéologique); Copán Site (Honduras); Copán